(untitled) (Huellas, 2015)
The social, economical and environmental situation of the West of theprovinceofLa Pampahas been, during the last decades, a matter of concern for the citizenship and also an area of political and state intervention. The idea of analyzing those decades from a territorial and genre perspective led to a preliminary research on the population living conditions. This paper presents both theoretical and methodological approaches that contribute to identify the power rationale and relations, which are recreated in the institutional actions and intentions regarding the vulnerable population of two settlements in the West of the province. More specifically, the issue focuses on identifying the multiple dimensions constituting the social vulnerability conditions of women living in the Departments of Limay Mahuida,La Pampa.